2021
DOI: 10.3389/fonc.2021.641343
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Landscape of Long Non-Coding RNAs in Colorectal Cancer Metastasis

Abstract: Colorectal cancer (CRC) is one of the most common gastrointestinal cancers, with extremely high rates of morbidity and mortality. The main cause of death in CRC is distant metastasis; it affects patient prognosis and survival and is one of the key challenges in the treatment of CRC. Long non-coding RNAs (lncRNAs) are a group of non-coding RNA molecules with more than 200 nucleotides. Abnormal lncRNA expression is closely related to the occurrence and progression of several diseases, including cancer. Recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 232 publications
0
23
0
Order By: Relevance
“…Involvement of a variety of genetic and epigenetic changes has been reported in CRC initiation and progression (Okugawa et al, 2015;Siskova et al, 2020). LncRNAs have been reported to play important roles in epigenetic alterations, revealing their potential as novel targets for CRC prevention and treatment (Chen et al, 2021;Liao et al, 2021). Gong et al (2019) found that CRC patients in stages I-II presented with lower levels of tumor DUXAP8 than those in stage III-IV, and patients with larger tumor sizes expressed higher levels of DUXAP8.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Involvement of a variety of genetic and epigenetic changes has been reported in CRC initiation and progression (Okugawa et al, 2015;Siskova et al, 2020). LncRNAs have been reported to play important roles in epigenetic alterations, revealing their potential as novel targets for CRC prevention and treatment (Chen et al, 2021;Liao et al, 2021). Gong et al (2019) found that CRC patients in stages I-II presented with lower levels of tumor DUXAP8 than those in stage III-IV, and patients with larger tumor sizes expressed higher levels of DUXAP8.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The previous studies have indicated that many lncRNAs are dysregulated in cancers (Iyer et al, 2015;Yan et al, 2015). Aberrant expression of lncRNAs is associated with tumor growth (Zhou et al, 2020), metastasis (Liao et al, 2021), angiogenesis (Jin et al, 2020), chemotherapy resistance (Ferretti and LeĂłn, 2021), and metabolism (Xu et al, 2021). Therefore, lncRNAs are regarded as important regulators of the pathological processes in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since colorectal cancer is a multifactorial disease, studies aiming to reveal the molecular changes associated with this type of cancer can provide potential preventative and therapeutic strategies for this disease [26][27][28]. In colorectal cancer, a few lncRNAs have been identified as potential diagnostic and therapeutic targets [29,30]. In present study, we found that SNHG10 expression was up-regulated in colorectal cancer, and downregulation of SNHG10 inhibited the ability of HCT116 and DXH-1 cells proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%